Whispering to Witches - Dale, Anna. (New York Bloomsbury, 2004)
On his way to spend Christmas at his mother's house in Canterbury, England, Joe meets a young witch named Twiggy and becomes part of a mystery involving a missing page from an ancient book of magic.
5 - 9
Keywords: Witches - Fiction; Magic - Fiction; England - Fiction